Capability and Cooperation As Pre-Requisites For Sustainability: Leveraging Cooperative Strategies for Sustainable Organizational Growth (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Organizations  need to  continually  change  in  order  to  survive  and  to  grow;  this  is  especially  true  in  the competitive  markets  andin  market  based economies.  However,  over emphasis  on change  can be  a  deterrent  to organizational growth. It  is thereforeessential  to  correctly identify  areas and  reasons for  change. Critical  decisions of  identifying the  areas, and  order of  change that would lead  to a path  of sustainability  and  growth  for  an  organization  require  a  decisive assessment  process.  At  each  phase  of  a decision making  process, there  are numerous  nondeterministic choices  and the  certainty of  success may  be influenced  by  manyexternal  factors.  External  factors affecting an organization include market forces such as, competition, user demand, and suppliers, in addition  to political,  legal,  and environmental  factors.  These in  turn influence  internal efficiencies  of  its components:  divisions, product lines, and  Strategic  Business  Units-  grouped together as Value  Components  (VC).  In  this paper, we present  methodologies for organizations  to  recognize areas  and rationale  for change,  and to  identify options  available for  change. Our  model for these methodologies  is  generic as  it explores  effective ways  to leverage  cooperative strategies  for competitiveness  and  applies to all industries.  We elaborate  on issues  and knowledgebase required for  critical VC  of a corporation,  and on  understanding  the limits of  efficiencies  that  can  be  achieved.  A  conceptual framework  that  emerges  from  the  model provides  systematic guidelines for critical  decision making.